Skin coverage of the anterior region of the knee with an anterolateral reverse flow thigh flap based on the perforating artery of the transverse branch of the lateral femoral circumflex artery: a case report - Fábio Santiago de Macedo; Jairo Zacchê de Sá; Kyldery Wendell Moura Cavalcante; Rafael Neves de Souza (Revista Brasileira de Cirurgia Plástica, 2023)
The patella is an uncommon place for the appearance of bone tumors, benign or malignant, and pseudotumoral lesions. In the literature, there is a small amount of work on this topic. This case report is about a patient with a metastatic tumor in the patella and reconstruction of the deformity with an anterolateral reverse flow thigh flap. Skin and soft tissue reconstruction in the region around the knee are often challenging for the plastic surgeon and aim to cover the exposed bone, preserving the joint function of the knee and providing a good esthetic result. There is an option for the use of free flaps, where there is a need for adequate material and trained staff. However, the vascular anastomosis region at the back of the knee makes the procedure even more complex. The anterolateral reverse thigh fasciocutaneous flap, first described in 1990 by Zhang et al., appears to be an effective and reliable option for reconstructing defects around the knee. It has a long vascular pedicle length and the availability of soft parts. There are some anatomical variations in which the cutaneous perforator does not originate from the descending branch. This report presents a patient with a skin perforator originating from the transverse branch of the lateral femoral circumflex artery, with an acceptable aesthetic result for skin coverage in the anterior region of the knee.